Integrative review on olfactory disfunctions caused by COVID-19 (Research, Society and Development, 2022)
The study aims to gather and synthesize scientific information related to olfactory dysfunctions caused by SARS-CoV-2 (COVID-19). This is an integrative literature review carried out from scientific journals published from August to December 2021. Original articles with systematic literature reviews, retrospective observational studies, prospective descriptive studies, case-control studies and meta-studies were included meta-analyses. It was concluded that symptoms related to olfactory dysfunctions caused by COVID-19 vary according to age, sex, genetics, stage of the disease and pre-existing comorbidities. The mechanism of action by the virus to promote sensory changes is still uncertain. The main evidence suggests viral dissemination through the olfactory cleft neuroepithelium, with consequent infiltration in the olfactory bulb or neural loss mechanism, with direct damage to the olfactory sensory neurons. Given the complexity of the infection caused by COVID-19 it is essential to continue thematic research, especially in relation to the new variants of SARS-CoV-2.